Mengatasi Permasalahan Administrasi Pernikahan dan Kependudukan Melalui Inovasi Pelayanan Publik Jalan Berdua di Kota Pasuruan - Aulia Annisa Nabila; Ali Roziqin; Muhammad Kamil (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2024)
The marriage registration process is one of the important stages in validating a marriage legally. This process often requires complex efforts, takes time and costs significant money, especially for couples who come from areas far from population administration offices or religious courts. To overcome this challenge, the Pasuruan City Government has introduced an innovative Double Road service. This service allows couples to register their marriage as well as change their marital status on their Family Card and Electronic KTP documents. This second road innovation has the impact of improving population administration services regarding changes in marital status on Family Cards and Electronic KTPs. This research aims to describe the problems that arise in the Innovation program and the efforts made to overcome the problems that arise in the Dual Road Innovation program in Pasuruan City. This research uses a qualitative descriptive approach with primary and secondary data sources. Primary data was obtained through interviews, observation and documentation related to Jalan Berdua innovation. Secondary data is in the form of documents related to research. Data collection techniques involve observation, open interviews, and documentation. This research will provide an overview of the problems faced in implementing the Double Road Innovation in Pasuruan City and the efforts that have been made to overcome them. The results of this research are: Overall, the Jalan Berdua program in Pasuruan City is a successful example of how innovation in population administration services can improve efficiency, accessibility, community satisfaction, inter-agency cooperation, and effective use of data.